2017
DOI: 10.22521/edupij.2017.62.5
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Relationships between Teachers’ Critical Thinking Dispositions and Their Perceptions of Occupational Professionalism

Abstract: The purpose of this descriptive study is to explore the relationships between teachers' critical thinking dispositions and their perceptions of occupational professionalism. The sample of the study has consisted of 242 teachers specified from the population of upper-secondary school teachers working in Mentese, Mugla, Turkey. The data of the study were collected through the administration of the UF/EMI Critical Thinking Dispositions Assessment scale and the Teachers' Occupational Professionalism scale. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…Furthermore, it is true that without proper practice, the knowledge of critical thinking skills alone is insufficient to allow them to practice the skills effectively in the classrooms, especially in teaching literature. Numerous studies suggested that the acquisition of critical thinking skills is not autonomous (Ekinci and Ekinci, 2017) and knowledge gained should be acquired and practiced. The results from a few studies such as Palavan (2020) and Ekinci and Ekinci (2017) indicated that even those who possess the skills could not effectively use critical thinking skills in many situations requiring them to think critically.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is true that without proper practice, the knowledge of critical thinking skills alone is insufficient to allow them to practice the skills effectively in the classrooms, especially in teaching literature. Numerous studies suggested that the acquisition of critical thinking skills is not autonomous (Ekinci and Ekinci, 2017) and knowledge gained should be acquired and practiced. The results from a few studies such as Palavan (2020) and Ekinci and Ekinci (2017) indicated that even those who possess the skills could not effectively use critical thinking skills in many situations requiring them to think critically.…”
Section: Discussionmentioning
confidence: 99%
“…Cekin [25] found that the prospective culture/religion teachers at Ankara University of Turkey had good critical thinking dispositions. Ekinci and Ekinci [26] reported that the critical thinking dispositions of teachers were closely related to the teachers' perception of professional works.…”
Section: B Discussionmentioning
confidence: 99%
“…Even though these skills are a prerequisite for critical thinking, it is not enough for the individual to have these skills for realizing critical thinking. The studies show that even though individuals have these skills, they are unable to use them in many cases (Ekinci & Ekinci, 2017). Because critical thinking comprises several dispositions along with these skills and requires coexistence of skills and dispositions.…”
Section: Ijoess June 2019 553mentioning
confidence: 99%
“…which includes trusting in the skill of reasoning (Ertaş Kılıç and Şen, 2014;Ekinci and Ekinci, 2017). This is a significant result.…”
Section: Ijoessmentioning
confidence: 99%
See 1 more Smart Citation